Proceedings of the International Conference on Business Law and Local Wisdom in Tourism (ICBLT 2018) 2018
DOI: 10.2991/icblt-18.2018.22
|View full text |Cite
|
Sign up to set email alerts
|

The Locus Sulus Concept as Local Wisdom in Building Planning and Development

Abstract: The aim of this study is to examine the relationship between Article 6 paragraph (1) letter b Act number 26 Year 2007 on Spatial Planning, which states that spatial arrangement is organized by taking into account the cultural element and Regional Regulation of Bali Province number 16 Year 2009 on Bali Regional Spatial Plan Year 2009-2029, which lists the principle of local wisdom through the philosophy of Tri Hita Karana. The method of analysis used in this study is prescriptive analysis method that is to exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The results study conducted by Senastri (2021) in analysing the concept of regulations of spatial planning in rural areas based on local wisdom in a sustainable national spatial planning system, showed the results that regulating sustainable spatial planning in rural areas based on local wisdom, the cultural dimension should precede other dimensions as it contains a set of values. Meanwhile, the results study conducted by Ulfatdjanovna (2022) in examining the role of legal culture in the development of modern society, showed that legal culture is one of the elements of universal culture, and just as national spiritual culture gives integrity and integration to the whole society, legal culture also determines the principles of legal behaviour of the individual, the system of legal values.…”
Section: Introductionmentioning
confidence: 99%
“…The results study conducted by Senastri (2021) in analysing the concept of regulations of spatial planning in rural areas based on local wisdom in a sustainable national spatial planning system, showed the results that regulating sustainable spatial planning in rural areas based on local wisdom, the cultural dimension should precede other dimensions as it contains a set of values. Meanwhile, the results study conducted by Ulfatdjanovna (2022) in examining the role of legal culture in the development of modern society, showed that legal culture is one of the elements of universal culture, and just as national spiritual culture gives integrity and integration to the whole society, legal culture also determines the principles of legal behaviour of the individual, the system of legal values.…”
Section: Introductionmentioning
confidence: 99%